Vulnerability of populations to malaria after indoor residual spraying is withdrawn from areas where its use has previously been sustained: a protocol for a systematic review. Issue 10 (26th October 2022) - Orishaba, Philip; Kayongo, Edward; Lusiba, Pastan; Nakalema, Caroline; Kasadha, Peter; Kirya, Perez; Kawooya, Ismael; Mijumbi-Deve, Rhona
Abstract : Introduction: With its proven effectiveness, indoor residual spraying (IRS) as a malaria vector control strategy forms one of the reliable vector control strategies, especially when at least 80% of the population is covered. However, to date, there is uncertainty regarding the consequences of IRS withdrawal on malaria control when there is no clear exit strategy in place. Therefore, there is a need to comprehensively update literature regarding malaria burden indicators when IRS is withdrawn following sustained use. Methods and analysis: This protocol follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A systematic search of studies published between 2000 and 2022 will be performed in CINAHL, Embase, MEDLINE, ProQuest, PsychInfo, Scopus and OpenGrey. Preset eligibility criteria will be used to identify studies for inclusion by two independent reviewers. Title/abstracts will first be screened and potentially eligible ones screened using their full-text publications. Any conflicts/discrepancies at the two stages will be resolved through regular discussion sessions. Included studies will be extracted to capture study and patient characteristics and relevant outcomes (malaria incidence and malaria vector abundance). Relevant tools will be used to assess the risk of bias in the studies measuring the impact of withdrawal. A meta-analysis will be performed if sufficient homogeneity exists; otherwise, data arising will be presented using tables and by employing narrative synthesis techniques. Heterogeneity will be assessed using a combination of visual inspection of the forest plot along with consideration of the χ 2 test and I 2 statistic results. Ethics and dissemination: Ethics approval is not applicable for this study since no original data will be collected. The results will be disseminated through peer-reviewed publications and conference presentations. Furthermore, this systematic review will inform the design of exit strategies for IRS-based programmes in malaria-endemic areas. PROSPERO registration number: CRD42022310655.